Factors affecting Maternal-care during labour at maternity centres of Karachi, Pakistan: Exploratory study - Nirmal Shahzaib; Tazeen Saeed Ali; Nousheen Akber Pradhan; Farina Abrejo; Shahnaz Shahid; Amir Ali Samnani (Journal of the Pakistan Medical Association, 2021)
Each year around 529,000 women die worldwide due to harmful consequences of childbirth in developing countries. Thus, this study aimed to explore barriers and facilitators that influence the provision of quality care during labor at maternity centers of Karachi, Pakistan. The qualitative exploratory study design was used to explore such factors from public and private maternity health facilities of Karachi, Pakistan. In-depth interviews were conducted through purposive sampling by using validated semi-structured interview guide. Data was analyzed using content analysis manually. Among major barriers; unhygenic environment, lack of basic equipment, supplies and medicine, unprofessional attitude of staff, physical infrastructre and shotrage of staff were explored. Among facilitators; Caring and supportive attitude of healthcare personnel during labor were identified. Continuous...